2020
DOI: 10.1177/2040620720965411
|View full text |Cite
|
Sign up to set email alerts
|

Co-transplantation of mesenchymal stem cells makes haploidentical HSCT a potential comparable therapy with matched sibling donor HSCT for patients with severe aplastic anemia

Abstract: The application of haploidentical hematopoietic stem cell transplantation (HSCT) with mesenchymal stem cell (MSC) infusion as a treatment regimen for severe aplastic anemia (SAA) has been reported to be efficacious in single-arm trials. However, it is difficult to assess without comparing the results with those from a first-line, matched-sibling HSCT. Herein, we retrospectively reviewed 91 patients with acquired SAA. They received HSCT from haploidentical donors combined with MSC transfer (HID group). We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
3
17
1
Order By: Relevance
“…Taking quality of life into consideration, cGvHD was the major concern of HID-HSCT compared to IST. However, in line with other studies in China (4,5,28), our work reported a culminative incidence of estimated 5-year moderate to severe cGvHD after HID-HSCT of 9% (95% CI, 0-18) vs. 3% (95% CI, 0-5) (p = 0.076) after MSD-HSCT, and no patients had severe cGvHD in the HID group. Cardiac toxicity related to high-dose CY is of great concern to patients with SAA who are elderly or have poor cardiac function due to anemia with lethal cardiotoxicity up to 2.3% (29).…”
Section: Discussionsupporting
confidence: 91%
“…Taking quality of life into consideration, cGvHD was the major concern of HID-HSCT compared to IST. However, in line with other studies in China (4,5,28), our work reported a culminative incidence of estimated 5-year moderate to severe cGvHD after HID-HSCT of 9% (95% CI, 0-18) vs. 3% (95% CI, 0-5) (p = 0.076) after MSD-HSCT, and no patients had severe cGvHD in the HID group. Cardiac toxicity related to high-dose CY is of great concern to patients with SAA who are elderly or have poor cardiac function due to anemia with lethal cardiotoxicity up to 2.3% (29).…”
Section: Discussionsupporting
confidence: 91%
“…In line with Liu et al. ( 24 ), our results reported an acceptable incidence of sPGF after haplo-HSCT for AA. In contrast, Japanese colleagues reported a higher incidence of sPGF of 15% in 49 pediatric AA patients, which included 3 transplantations from matched sibling donors (20.0%), 3 from unrelated donors (10.3%), and 1 from haploidentical donor (20%) ( 25 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, the negative effects of bone marrow hematopoietic microenvironment damage and delayed immune reconstitution may lead to poor stem cell engraftment, and increase the rate of postoperative infection and recurrence ( Bair et al, 2020 ; Mallhi et al, 2020 ). A series of animal and clinical trials showed that HSCT or cord blood transplantation (CBT) combined with infusion of UC-MSCs is able to promote hematopoietic engraftment and reduce the occurrence GVHD ( Liu et al, 2020c ; Yang et al, 2020 ). It was reported that UC-MSCs promote myeloid-derived suppressor cell proliferation by secreting HLA-G to reduce acute GVHD after HSCT ( Yang et al, 2020 ).…”
Section: Application Of Uc-mscs In Hematologic Diseasesmentioning
confidence: 99%
“…UC-MSCs produce an immunosuppressive isoform of HLA-1, do not express HLA-DR and lack costimulatory signaling systems and immune response-related surface antigens such as CD40, CD40L, CD80, and CD86, which indicate that UC-MSCs can be tolerated in allogeneic transplantation ( Wang et al, 2014 ). There were no reports of any toxicity or side effects when UC-MSCs were injected into laboratory animals in pre-clinical trials ( Fan and Zhang, 2011 ), or were used to treat aplastic anemia ( Xu et al, 2018 ; Liu et al, 2020c ), leukemia ( Kang-Hsi et al, 2013 ; Wu Y. et al, 2013 ) in clinical studies. This indicates that it is safe enough to use allogeneic MSCs after the HLA molecule is detected.…”
Section: Application Of Uc-mscs In Hematologic Diseasesmentioning
confidence: 99%